The Effect of the Guided Inquiry Model on Mathematics Skills of Fifth-Grade Elementary School Students - Ayu Putri Indraswari; Gusti Ngurah Sastra Agustika; Anak Agung Ayu Dewi Sutyaningsih (Undiksha Press, 2025)
This study was motivated by the low mathematical proficiency of elementary school students, which is attributed to the lack of varied instructional models that actively engage students in learning. The aim of this research is to examine the influence of the guided inquiry model on the mathematical proficiency of fifth-grade elementary students. This study employed a quantitative approach with a quasi-experimental design. The population consists of all fifth-grade students from 13 classes, totaling 360 students. The sample was selected using cluster random sampling. Two classes were chosen as samples, one serving as the control group and the other as the experimental group. The method and instrument used for data collection was a test. The data analysis techniques applied were descriptive and inferential statistical analysis. The results of the study show that students who participated in learning through the guided inquiry model experienced a significant improvement in mathematical proficiency compared to those who were taught using conventional methods. The implications of this research suggest that the guided inquiry model can serve as an effective alternative instructional strategy for enhancing students' conceptual understanding and mathematical thinking skills in elementary schools.